Sprawozdanie z konferencji Kodeks Spółek Handlowych po 5 latach Wrocław 25-26 września 2005 roku - Gawrysiak-Zabłocka, Aleksandra (Zeszyty Prawnicze, 2017)
Sprawozdanie z konferencji Kodeks Spółek Handlowych po 5 latach Wrocław 25-26 września 2005 roku